Indications and Complications of Implant Removal from Extremities in Adult Orthopaedic Patients – A Retrospective Study in a Tertiary Care Hospital. (Journal of Pakistan Orthopaedic Association, 2022)
Objectives: To determine the indications and complications of implant removal from extremities in adult Orthopaedic patients in Abbasi Shaheed Hospital Karachi.Methods: This retrospective Cohort study was conducted in Orthopedics department Abbasi Shaheed Hospital Karachi. The medical records of all adults patients fulfilling the inclusion criteria who were operated for implant removal were reviewed. The review period extended from 21st January 2019 to 9th January 2021. The indications of implant removal, per operative and post operative complications of implant removal were noted in each case.Results: We reviewed the record of 64 patients. The mean age was 33±13.3 years. Male patients were 47(73.4%) and females were 17(26.5%). The most common indication of implant removal was infection(23%,n=23.4%) and pain(20.3%,n=13).The most common implant removal was locking compression plates in 19 (29.6%) patients followed by 3.5mm dynamic compression plates in 13(20.3%) and interlocking nail in 12(18.7%) patients. Tibia was the most commonly involved(28.1%,n=18) bone. Per operative complications were difficulty to access the implant in 8(12.5 %) cases, screw breakage in 5(7.8%) patients and implant breakage in 3(4.6%) patients. Post operatively 16(25%) patients were complaining of limb pain while 12(18.7%) patients had persistent local infection.Conclusion: The most common indication of implant removal was infection in our series. Difficulty to access the implant and screw breakage were the most common per operative complications while pain and persistent local infection were the most common post operative complications.